THE ROLE OF BRAND AWARENESS IN MEDIATING THE EFFECT OF ADVERTISING ATTRACTIVENESS ON PURCHASE INTENTION(A Study of Prospective Consumers of Kopi Kulo in Denpasar City) - I Wayan Diva Indrayana; Gede Bayu Rahanatha; I Gst. Ayu Kt. Giantari (Adisam Publisher, 2026)
This study aims to examine the effect of advertising appeal on purchase intention with brand awareness as a mediating variable among prospective consumers of Kopi Kulo in Denpasar City. This study was conducted by distributing questionnaires to 100 respondents who interacted with Kopi Kulo advertisements. The data were analyzed using multiple linear regression with a path analysis approach, and hypothesis testing was carried out through simultaneous testing (F-test), partial testing (t-test), and the coefficient of determination test (R²). The results show that advertising appeal has a positive and significant effect on purchase intention and brand awareness. Brand awareness is proven to be able to significantly mediate the effect of advertising appeal on purchase intention. Theoretically, this study contributes to the development of the literature related to the relationship between advertising appeal, brand awareness, and purchase intention. Practically, the results of this study can serve as a consideration for the management of Kopi Kulo Denpasar in designing more attractive and effective advertising strategies, thereby enhancing brand awareness and optimally encouraging consumer purchase intention.